Eye-Tracking Study on Reading Fluency in Relation to Typeface Pleasantness Influenced by Cross-Modal Correspondence Between Taste and Shape - Tanja Medved; Anja Podlesek; Klementina Možina (Applied Sciences)
Reading fluency depends on the typographic design. Letters can have different shapes that evoke different feelings in the reader and influence reading fluency. Previous studies that explored the link between typeface shape and taste and its impact on reading and readers’ attitudes mainly focused on shorter texts or individual words. In contrast, our study investigated how the taste (sweetness) attributed to the typeface is related to reading fluency and the pleasantness of the typeface during reading longer texts, and whether these relationships are the same in children and adult readers. We found that readers of both age groups perceived rounded letters as sweeter than angular letters. The perceived sweetness correlated positively with the pleasantness of the typeface and reading fluency. Younger readers showed a higher general rating of sweetness and a stronger relationship between the perceived sweetness and the pleasantness of the typeface than older, more experienced readers. This suggests that the sweeter and more pleasant the typeface is perceived to be, the faster it can be read. When fast processing of longer texts is required, we recommend the use of rounded typefaces with more organic shapes, including serif typefaces with some characteristics of old-style typefaces, rather than using angular, sans serif typefaces.